Upaya Peningkatan Kinerja Departemen Warehouse di PT. X - Prayogo, Andreas; Sutapa, I Nyoman (Jurnal Titra, 2015)
PT. X is a car component manufacturer. The problems faced by PT. X in receiving area warehouse X 2,5 such as lack of storage capacity, FIFO system is not running, time consuming unloading, and bottleneck in the arrival supplierâs area. The 5S is applied to overcome those problems. The root causes of the problems are the lack of storage capacity and there is no schedule for supplierâs arrival. Therefore this research suggests to relayout the warehouse and makes a schedule for the supplierâs arrival. As the implementation results, the storage capacity is increased from 410 to 536 units and the unloading time is reduced from 25 minutes to less than 5 minutes. Additionally, the defect is reduced, and the FIFO system is running well.